Respons Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq) Pada Media Tanah Ultisol dengan Aplikasi Pupuk NPK dan Pupuk Hayati Mikoriza di Pembibitan Utama - Zulfansyah, Ichpan; Pulungan, Nurliana (Universitas Batanghari, 2025)
Providing NPK fe rtilize r and mycorrhiza with Ultisol soil media aims to de te rmine the effect of inte raction be twe en NPK fe rtilize r and mycorrhiza, single effect mycorrhiza. Single influence of NPK pupul on the growth of oil palm se e dlings in main nurse ry. This research was carrie d out in the experimental garden at the Faculty of Agriculture Jambi University from August 2023 to Octobe r 2023. This re search carrie d out using a Randomize d Block De sign (RAK) with a patte rn factorial of two factors. and e ach combination is re pe ate d 3 time s. Factor first NPK fertilize r with thre e dose s of 10 g 6.7 g 3.4 g. and re comme ndation of 10 g. Se cond factor mycorrhiza dose with thre e tre atme nts of 10 g 6.7 g 3.4 g. and recommendation of 10 g. Variable Obse rvations such as seedling he ight, number of le ave s, ste m diame te r, rachis le ngth, and leaf area. The results of this re se arch show that the combination of mycorrhizal fertilize r and NPK fe rtilize r dose s can increase the growth of oil palm se e dlings in the main nurse ry. the combination of 10 g of mycorrhizal fe rtilize r + 10 g of NPK fe rtilize r gave the be st growth compare d to without a combination of mycorrhizal fe rtilize r and NPK fe rtilize r. Giving 10 g of mycorrhizal fe rtilize r + 10 g of NPK gave the highe st re sults in the parame te rs of plant he ight, numbe r of le ave s, le af are a. The interaction between NPK fertilizer and mycorrhizal biofertilizer treatments had a significant effect on the parameters of plant height and diameter of oil palm seedling tubers in the main nursery.